Detumbling of a non-cooperative target with unknown inertial parameters using a space robot. Issue 12 (15th June 2019) - Gangapersaud, Rabindra A.; Liu, Guangjun; de Ruiter, Anton H.J.
Highlights: Detumbling of a non-cooperative target with unknown inertial parameters using space robot is addressed. Proposed robust detumbling controller uses real-time estimates of bounds on the target's inertial parameters. The detumbling strategy respects grasping force/torque limits of space robot. Abstract: The detumbling of a non-cooperative, tumbling target by a space robot for the purpose of performing on-orbit servicing is a challenging and risky endeavour. The formulation of a detumbling control strategy must respect end-effector force/torque limits of the space robot without prior knowledge of the target's inertial parameters (mass, inertia tensor, location of center of mass). Prior studies have formulated detumbling strategies with the assumption of accurate knowledge of the target's inertial parameters. However, obtaining accurate estimates of the target's inertial parameters is difficult, and parameter uncertainty may lead to instability and violation of the end-effector's force/torque limits. In this paper, a novel detumbling strategy is presented to detumble targets without prior knowledge of their inertial parameters. Detumbling of the target is achieved by controlling the space robot to follow a reference force/torque that is designed to detumble the target while respecting force/torque limits at the end-effector, without the use of the target's inertial parameters. To ensure stable detumbling of the target, a robust compensator is designed based on bounds of the target's unknown inertial parameters. Furthermore, in order to reduce the robust control gains, bounds on the target's unknown inertial parameters are estimated in real-time once the post-grasping detumbling process starts. Stability proof of the closed-loop system has been provided. Numerical simulations have been conducted, and the results have demonstrated the effectiveness of the proposed method.